2020
DOI: 10.4149/bll_2020_117
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of MMP2, TIMP2, MMP9 and TIMP1 in abdominal aortic aneurysm

Abstract: OBJECTIVES: Abdominal aortic aneurysm (AAA) and its complications are among the most serious cardiovascular diseases and its occurrence has risen sharply in recent years. The aim of this pilot study is to explore the relationship between the methylation of matrix metalloproteinases and tissue inhibitors of the metalloproteinases genes' promoter region, and abdominal aortic aneurysm (AAA) through the detection of the methylation status of MMP2, TIMP2, TIMP1, and MMP9 genes in peripheral blood. METHODS: The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…The position of the AP-1 sequence of TIMP2 is important, as treatment with 12-O-tetradecanoylphorbol-13-acetate only provokes a response within specific AP-1 consensus regions [ 38 ]. Methylation influences TIMP2 gene expression [ 39 , 40 ], as well as TIMP1 [ 41 ] and TIMP3 [ 42 ]. Further, hypermethylation of the TIMP2 promoter causes transcriptional repression of TIMP2 levels in many types of tumors, including lymphoma [ 43 ] and prostate cancer [ 44 ], resulting in tumor metastasis through MMP activation.…”
Section: Timp2: Function Regulation and Structurementioning
confidence: 99%
“…The position of the AP-1 sequence of TIMP2 is important, as treatment with 12-O-tetradecanoylphorbol-13-acetate only provokes a response within specific AP-1 consensus regions [ 38 ]. Methylation influences TIMP2 gene expression [ 39 , 40 ], as well as TIMP1 [ 41 ] and TIMP3 [ 42 ]. Further, hypermethylation of the TIMP2 promoter causes transcriptional repression of TIMP2 levels in many types of tumors, including lymphoma [ 43 ] and prostate cancer [ 44 ], resulting in tumor metastasis through MMP activation.…”
Section: Timp2: Function Regulation and Structurementioning
confidence: 99%
“…Доказана ассоциация минорного аллеля 5А rs3025058 гена MMP-3 с аневризмой брюшной аорты (ОШ=1,48; 95% ДИ: 1,23-1,78, р=0,00395). В работах [7][8][9] эти результаты подтверждены.…”
Section: основные результатыunclassified
“…This opinion is addressed in a recent article, which evaluates the global methylation level in AAA patient-derived peripheral blood mononuclear cells (PBMCs) and compares it with that in PBMCs from normal subjects [ 40 ]. The study conducted by Skorvanova et al revealed no association of AAA development with DNA methylation of gelatinases and their tissue inhibitors (e.g., MMP2, TIMP2, TIMP1, and MMP9) [ 49 ].…”
Section: Epigenetic Regulation Of Aaasmentioning
confidence: 99%